Comprometimento afetivo e entrincheiramento organizacional dos auditores: um estudo cross-cultural entre Brasil e México - Flores, Ruben Flores (2018)
New theories and advances in society have transformed the relationship between man and his work throughout the last decades. In this context the individualorganization links are being studied. Thus, work commitment and entrenchment appear as divergent behavioral attitudes, causing significant personal, organizational and social impacts (CARSON, CARSON, BEDEIAN, 1995); for Meyer and Allen (1991), organizational commitment is conceived as a psychological state that characterizes the attachment of individuals to the organization. On the other hand, entrenched people remain in the organization out of necessity or lack of alternatives. The objective of this study is to analyze which type of bond, whether affective commitment or organizational entrenchment, are preponderant in the permanence of audit professionals of Brazil and Mexico of the Big Four. Because of the prestige they have in the professional auditing area, as well as their investment in staff training, it is important to conduct research on their workers bonds with the organization. The approach of the problem of this research can be characterized, due to its nature, as qualitative, due to its objectives as exploratory and the typology of multicase study. The instrument used was the interview, carried out through an in-depth semi-structured script. The study reached the target of 10 Big Four audit workers in the Mexico area, and 10 in Brazil. The software Atlas.ti - version 7.0, appropriate for the qualitative analysis of interviews, was used for content analysis and conceptual ordering. At the end of the present study, it is concluded that both the auditors in Brazil and those in Mexico are mainly positively linked to the Big Four where they work, mainly due to the professional growth that can be obtained within them. On the contrary, it can be concluded that neither of the two groups shows a high level of entrenchment, on the contrary, in both groups the costs linked to quitting do not represent a bond that forces the individual to stay in the organization. From a general point of view it can be concluded that the entrenchment does not represent a problem in the Big Four of Brazil and Mexico today.